Penguatan Kapasitas Badan Usaha Milik Desa (BUM Desa) dalam Rangka Optimalisasi Keputusan Investasi di Kabupaten Serang - Ria Ekanindya Widyaningsih; Krist Setyo Yulianto; Halim Dedy Perdana (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service (PkM) activity aims to increase the capacity of Village-Owned Enterprises (BUM Desa), especially Village Financial Institutions (LKD), in making safe, rational, and sustainable investment decisions in the Serang Regency area. The main problems faced by BUM Desa include limited understanding of investment instruments, risk management, and adequate investment feasibility analysis capabilities. To answer these challenges, this activity was carried out online through a collaboration between the State Financial Polytechnic STAN and the Open University, with a participatory socialization approach. The speakers came from the Directorate General of Financing and Risk Management (DJPPR) of the Ministry of Finance and Bank Rakyat Indonesia Danareksa Sekuritas, who provided practical and strategic insights related to village investment. The results of the activity showed a significant increase in participants' investment literacy, the formation of strategic networks between stakeholders, and a high commitment to the application of knowledge at the village institutional level. The evaluation showed that 92% of participants experienced an increased understanding of investment and risk management concepts, while 90% expressed readiness to apply the knowledge gained in institutional practice. These findings indicate that the digital approach is able to reach rural communities widely and effectively, despite methodological limitations such as the duration of implementation and the lack of direct interaction. Overall, this activity represents an effective model of academic and practical collaboration in supporting people-based economic development at the village level. It is hoped that this activity will be the foundation for the development of a sustainable village investment literacy program, as well as strengthen the role of Village BUM as a driving force for the local economy that is resilient and adaptive to financial market dynamics.